1973
DOI: 10.1017/s0033291700048509
|View full text |Cite
|
Sign up to set email alerts
|

Social structure and the ecological distribution of mental illness, suicide, and delinquency

Abstract: SUMMARYData on serious psychiatric illness (900 cases), suicide (150 cases), indictable crime (1,300 cases), and child welfare problems (800 cases) in individuals living in Brighton have been collected. Rates of these behavioural pathologies have been calculated for 19 wards in the city, and correlated with data collected in the 1966 Census. Results show that the behavioural pathologies are strongly intercorrelated and are associated with in-migrant areas containing rooming houses of poor quality. These areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…Separate evaluation of affective psychoses and neurotic depression is recommended. In contrast to our results, Bagley et al (1973) reported strong ecological correlations in Brighton between affective psychoses and depression as well as with other psychiatric diagnoses.…”
Section: Discussioncontrasting
confidence: 99%
“…Separate evaluation of affective psychoses and neurotic depression is recommended. In contrast to our results, Bagley et al (1973) reported strong ecological correlations in Brighton between affective psychoses and depression as well as with other psychiatric diagnoses.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of factors have been implicated as environmental precipitants, if not causes, of schizo phrenia. These include social isolation (Jaco, 1954), lack of control over living environment including both isolation and overcrowding (Magaziner, 1988;Lomas et a!, 1973) and various indices of low socio economic status (Bagley et a!, 1973;Dohrenwend, 1990). Such ideas emphasise the experience of deprived inner-city living, both in terms of psycho logical stressors and general poor physical health, rather than individual genetics, to explain the over representation of people who will, at some point, develop schizophrenia in this type of urban setting.…”
mentioning
confidence: 99%
“…These studies focused upon the relationship between mental illness and the urban environment, with particular attention to the spatial distribution of mental illness in different social areas of these cities. Some consistent findings of these studies have included: a concentration of people with schizophrenia in inner-city areas (Giggs, 1973;Dean & James, 1981); a more random distribution of people with manic depression (Dean & James, 1984;Taylor, 1974); and a correlation of incidence of particular disorders with social factors such as suicide and delinquency (Bagley et al, 1973;Bagley & Jacobson, 1976). These examples of ecological studies of mental illness demonstrate the spatial variability of mental illness, particularly within an individual city.…”
Section: The Geography Of Mental Healthmentioning
confidence: 88%